Development of cataclastic foliation in deformation bands in feldspar-rich conglomerates of the Rio do Peixe Basin, NE Brazil. (February 2018) - Nicchio, Matheus A.; Nogueira, Francisco C.C.; Balsamo, Fabrizio; Souza, Jorge A.B.; Carvalho, Bruno R.B.M.; Bezerra, Francisco H.R.
Abstract: In this work we describe the deformation mechanisms and processes that occurred during the evolution of cataclastic deformation bands developed in the feldspar-rich conglomerates of the Rio do Peixe Basin, NE Brazil. We studied bands with different deformation intensities, ranging from single cm-thick tabular bands to more evolved clustering zones. The chemical identification of cataclastic material within deformation bands was performed using compositional mapping in SEM images, EDX and XRD analyses. Deformation processes were identified by microstructural analysis and by the quantification of comminution intensity, performed using digital image processing. The deformation bands are internally non homogeneous and developed during five evolutionary stages: (1) moderate grain size reduction, grain rotation and grain border comminution; (2) intense grain size reduction with preferential feldspar fragmentation; (3) formation of subparallel C-type slip zones; (4) formation of S-type structures, generating S-C-like fabric; and (5) formation of C′-type slip zones, generating well-developed foliation that resembles S-C-C′-type structures in a ductile environment. Such deformation fabric is mostly imparted by the preferential alignment of intensely comminuted feldspar fragments along thin slip zones developed within deformation bands. These processes were purely mechanical (i.e., grain crushing and reorientation). No clays or fluids were involved in such processes. Highlights: Cm-thick deformation bands occur as single structures or as clusters. DB are non-homogeneous with moderate to pervasive cataclasis and grain alignment. Quartz grains occurs in a fine matrix composed of ultra-comminuted feldspar grains. Shear fabric resembles a S-C-C′-type structure developed in ductile environments. We propose five cataclastic foliation stages of deformation bands.